Enzyme-assisted calcium phosphate biomineralization on an inert alumina surface. (February 2015) - Aminian, Alieh; Pardun, Karoline; Volkmann, Eike; Li Destri, Giovanni; Marletta, Giovanni; Treccani, Laura; Rezwan, Kurosch
Graphical abstract: Abstract: In this study a bioinspired approach to induce self-mineralization of bone-like material on alumina surfaces is presented. The mineralizing enzyme alkaline phosphatase (ALP) is covalently immobilized by a carbodiimide-mediated chemoligation method. The enzymatic activity of immobilized ALP and its mineralization capability are investigated under acellular conditions as well as in the presence of human bone cells. Analytical, biochemical and immunohistochemical characterization show that ALP is efficiently immobilized, retains its activity and can trigger calcium phosphate mineralization on alumina at acellular conditions. In vitro cell tests demonstrate that ALP-functionalized alumina clearly boosts and enhances bone cell mineralization. Our results underpin the great potential of ALP-functionalized alumina for the development of bioactive surfaces for applications such as orthopaedic and dental implants, enabling a fast and firm implant osseointegration.